Finland 2015: balanced development : Government report to Parliament on Finland's future prospects - Suomi. Valtioneuvosto (Publication / The Prime Minister's Office, ISSN 0783-1609, 2001)
Summary (kuvailulehti).
Keywords: tulevaisuus : Suomi; väestö : Suomi; työvoima : Suomi; aluekehitys : Suomi